2021
DOI: 10.3390/pharmaceutics13060836
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antimicrobial Photodynamic Therapy in the Treatment of Periodontitis: A Systematic Review and Meta-Analysis of In Vivo Human Randomized Controlled Clinical Trials

Abstract: This systematic review and meta-analysis evaluated antimicrobial photodynamic therapy (aPDT) efficacy in periodontitis. The review protocol was conducted in accordance with PRISMA statements, Cochrane Collaboration recommendations and is registered in PROSPERO (CRD 42020161516). Electronic and hand search strategies were undertaken to gather data on in vivo human RCTs followed by qualitative analysis. Differences in probing pocket depth (PPD) and clinical attachment level (CAL) were calculated with 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 112 publications
1
11
0
Order By: Relevance
“…Dalvi et al, following a systematic review and meta-analysis, concluded that the efficacy of photodynamic therapy in improving treatment outcomes, when used in the non-surgical management of periodontitis, remains questionable. However, the results from most of the included studies demonstrated the efficacy of photodynamic therapy and that its role is more pronounced when combined with mechanical therapy (SRP) than when alone [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dalvi et al, following a systematic review and meta-analysis, concluded that the efficacy of photodynamic therapy in improving treatment outcomes, when used in the non-surgical management of periodontitis, remains questionable. However, the results from most of the included studies demonstrated the efficacy of photodynamic therapy and that its role is more pronounced when combined with mechanical therapy (SRP) than when alone [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inside the periodontal pocket for non-surgical therapy, we use a diode near-infrared laser with a wavelength between 800nm-980nm for coagulating gingivae (epithelial ablation inside the pocket) as an adjunct to SRP. Additionally, it results in complete removal of the inflamed epithelium and decreases the amount of pro-inflammatory agents [9,12,[28][29][30][31][32][33][34][35][36]. Appropriate laser wavelengths, with suitable protocols, probably can improve the periodontal status for a more extended period and likely limit the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…As the diode laser family is predominantly absorbed by mainly haemoglobin and pigmented bacteria and poorly absorbed by hydroxyapatite in teeth and bone, it is considered a safe and suitable treatment modality in sulcular debridement [38,39]. The photonic energy of an ablative diode laser in the diseased periodontal pocket results in various beneficial effects [35,37,[40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%